Frequency transformation of ultrafast laser pulses in metamaterials. (February 2019) - Kasumova, Rena J.; Amirov, ShSh
Abstract: The nonstationary parametric interaction of waves in negative-index metamaterials is studied in the second-order dispersion theory. A nonlinear interaction between a long pulse of a strong pump wave and an ultrashort pulse with quadratic phase modulation is considered. The results of calculating the shape of the spectrum of an excited signal wave are presented. A comparison is made with the case of interaction in an ordinary medium. It is shown that the effects of group-velocity dispersion and dispersive spreading in such materials lead to a narrowing of the spectrum of the excited wave. The presence of phase modulation of the exciting idler pulse promotes broadening of the central maximum of the spectrum of the excited signal wave. As the modulation factor increases, the fragmentation of the excited pulse is observed. Highlights: The nonstationary parametric interaction of waves in NIMs is studied in the second-order dispersion theory. The calculation of the excited signal wave spectrum and the comparison with the case in a conventional medium are presented. The presence of the exciting pulse phase modulation promotes broadening of central maximum of the excited wave spectrum. These results can be claimed in the development of frequency converters based on nonlinear negative-index metamaterials.